Lethargic crab disease: multidisciplinary evidence supports a mycotic etiology - Walter A Boeger; Marcio R Pie; Antonio Ostrensky; Luciana Patella (Memorias do Instituto Oswaldo Cruz, 2005)
Although lethargic crab disease (LCD) is causing massive mortalities in populations of the mangrove crab Ucides cordatus of Northeastern Brazil, the identity of its etiological agent was hitherto unknown. In this study we provide robust evidence suggesting that LCD is caused by an anamorph Ascomycota (Fungi). We examined specimens of U. cordatus collected from stocks affected by LCD. Histological and TEM methods detected the presence of hyphae, conidia, and condiophores in several host tissues. Moreover, the abundance of fungal stages is negatively associated with crab health. Finally, DNA was isolated from the fungus and a region of its 18S ribosomal gene was sequenced. Phylogenetic analyses not only confirm the diagnosis of the LCD fungus in crab tissues as an ascomycete, but also suggest a close relationship with members of the subphylum Pezizomycotina.